2020
DOI: 10.18632/aging.103307
|View full text |Cite|
|
Sign up to set email alerts
|

Hypoxia-preconditioned olfactory mucosa mesenchymal stem cells abolish cerebral ischemia/reperfusion-induced pyroptosis and apoptotic death of microglial cells by activating HIF-1α

Abstract: Among central nervous system (CNS) diseases, cerebral ischemic stroke is the most common cause of death and disability [1]. This condition has been successfully treated with tissue plasminogen activator (tPA) therapy. However, the reperfusion process may result in serious brain tissue damage [2], and has been an intractable challenge in stroke treatment. It is, therefore, crucial to elucidate the latent mechanisms of cerebral I/R injury. Cerebral I/R insult is often accompanied with inflammation [3]. In additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
36
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 43 publications
3
36
1
Order By: Relevance
“…Furthermore, remifentanil preconditioning led to a remarkable increase in HIF-1 level the cardiac tissues. Notably, recent studies have revealed that elevated HIF-1 could protect the organs from I/R-induced damage through potentiating antioxidant activity and facilitating cell survival [37][38][39]. Besides, cell model experiments showed that remifentanil preconditioning significantly reversed the increase in intracellular ROS accumulation and apoptosis of H9c2 cardiomyocytes triggered by hypoxia/reoxygenation exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, remifentanil preconditioning led to a remarkable increase in HIF-1 level the cardiac tissues. Notably, recent studies have revealed that elevated HIF-1 could protect the organs from I/R-induced damage through potentiating antioxidant activity and facilitating cell survival [37][38][39]. Besides, cell model experiments showed that remifentanil preconditioning significantly reversed the increase in intracellular ROS accumulation and apoptosis of H9c2 cardiomyocytes triggered by hypoxia/reoxygenation exposure.…”
Section: Discussionmentioning
confidence: 98%
“…Another in vivo investigation demonstrated that lymphocytes cocultured with human cord blood-derived multipotent stem cells (HCB-SCs) attenuated inflammasome activity in middle cerebral artery occlusion (MCAO) rats by suppressing NLRP3 inflammasome activation and promoting Tregs differentiation (Zhao et al, 2019c). In addition, a study on microglia revealed that hypoxia-preconditioned OM-MSCs suppressed pyroptotic death of microglia caused by cerebral ischemia-reperfusion insult by activating HIF-1α (Huang et al, 2020).…”
Section: Mscs and Pyroptosis In Ischemic Strokementioning
confidence: 99%
“…Interestingly, hypoxia pretreatment significantly increased the proliferation and chondrogenic differentiation of adipose tissue-derived stem cells but decreased their osteogenic differentiation in a vascular endothelial growth factor (VEGF)-dependent manner[ 25 ]. In parallel, hypoxia-preconditioned olfactory mucosa mesenchymal stem cells inhibits pyroptotic and apoptotic death of microglial cell in response to cerebral ischemia/reperfusion insult by activating hypoxia-inducible factor-1 (HIF-1) in vitro [ 26 ]. Hypoxia preconditioning of human dental MSCs empowers their immunoregulatory functions.…”
Section: Preconditioning Strategies Of Mscsmentioning
confidence: 99%